Living like you mean it : use the wisdom and power of your emotions to get the life you really want - Frederick, Ronald J., 1965- (Tantor Audio, 2019)
In Living Like You Mean It, author Ronald J. Frederick does a brilliant job of describing why people are so afraid of their emotions and how this fear creates a variety of problems in their lives. While the problems are different, the underlying issue is often the same.